Pelatihan Manajemen Pengelolaan Sampah di Desa Sumberagung Mantup Lamongan - Burhan Hakim, Ahmad; Rohman, M. Fathor; Fatwa, M. Dzawil; Pratama, Moch. Yeyen (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
This Real Work Lecture (KKN) and Community Service Program (PPM) broadly aim to provide insight, education and skills in the field of empowerment and training in dealing with problems in the community, one of which is waste management. Garbage is a part of human life. Garbage is an object / residual substance that is not used. Garbage should receive serious attention and handling. However, due to the lack of understanding of the community and the government, as well as the lack of costs and income for most people, this waste problem has been neglected. Currently, most people are aware of the bad effects of waste, including causing flooding, disease and odors that can interfere with life, but this is not balanced by the behavior of the people themselves. The purpose of this study is to try to find a way out of environmental sanitation problems, especially waste management in rural areas. This research was conducted in Sumberagung Village, Mantup District, Lamongan Regency with a population of 1,853 people. The data sources of this research are the heads of families from RT 1-5 Dsn. GempolWaru, namely 810 families. The members of the research sample amounted to 310 families. Collecting research data obtained primary and secondary. The results of the research that the authors get are a picture of good knowledge, fairly good attitudes and poor behavior from the people of Sumberagung Village towards waste. From the research conducted by the author, it can be concluded that the people of Sumberagung Village have good knowledge about waste, a fairly good attitude towards waste, but poor behavior towards waste, due to lack of attention from the local government which should be able to follow up on waste problems.